2006
DOI: 10.1111/j.1460-9592.2006.02095.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of intravenous or peritonsillar infiltration of ketamine for postoperative pain relief in children following adenotonsillectomy1

Abstract: Low dose ketamine given i.v. or by peritonsillar infiltration perioperatively provides efficient pain relief without side-effects in children undergoing adenotonsillectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
3
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 21 publications
2
65
3
3
Order By: Relevance
“…22 Of the 70 studies meeting inclusion criteria, 64 were suitable for inclusion in the quantitative analysis, and the remaining six were added to the qualitative analysis. These six studies reported data which were not useable in the quantitative analysis, such as median and range (two), mean only (one), mean and range (one), graphical data and SEM (one), and number of events of non-opioid rescue analgesia (one) were initially analyzed quantitatively, an additional 17 studies [70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86] were used to corroborate the results within the quantitative analysis, and the remaining six studies [87][88][89][90][91][92] were added to the qualitative analysis. All 70 studies had either low or unclear risks of bias in all six categories of the Cochrane Collaboration's tool for assessing risk of bias (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…22 Of the 70 studies meeting inclusion criteria, 64 were suitable for inclusion in the quantitative analysis, and the remaining six were added to the qualitative analysis. These six studies reported data which were not useable in the quantitative analysis, such as median and range (two), mean only (one), mean and range (one), graphical data and SEM (one), and number of events of non-opioid rescue analgesia (one) were initially analyzed quantitatively, an additional 17 studies [70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86] were used to corroborate the results within the quantitative analysis, and the remaining six studies [87][88][89][90][91][92] were added to the qualitative analysis. All 70 studies had either low or unclear risks of bias in all six categories of the Cochrane Collaboration's tool for assessing risk of bias (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Ketamine has been used to reduce post-operative pain following various surgical procedures like hernioraphy [20], abdominal hysterectomy [21], thoracotomy [22], circumcision [23], cesarean section [24], open cholecystectomy [25], appendectomy [26], tonsillectomy [27][28][29][30][31]. Recently ketamine has been used in oral and maxillofacial surgical practice as well [14,[32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have evaluated the effectiveness of ketamine administered locally to the peri-tonsillar region following tonsillectomy for postoperative pain management [27][28][29][30][31]. Tan et al [23] gave a subcutaneous ring infiltration of ketamine at the incision site before circumcision surgery and showed that the time interval until first analgesic demand was longer and the incidence of pain-free status during movement and erection was significantly higher than for the saline-treated analogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu çalışmaların çoğunda adenotonsillektomi operasyonları için en yüksek doz olarak 0.5 mg/kg intravenöz ketamin verilerek analjezik etki araştırılmıştır (7,(12)(13)(14)(15). Çalışmamız alt batın cerrahisi geçiren (minör cerrahi) 90 hastada yapılmış olup bu cerrahi tipinde ve bu sayıdaki hasta popülasyonunda yapılan bir adet çalışmaya rastlanmıştır (9).…”
Section: Discussionunclassified